Generation of narrow peaks in spectroscopy of charged particles - Dubbers, Dirk; Schmidt, Ulrich (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2016)
In spectroscopy of charged particles, narrow peaks may appear in continuous spectra if magnetic transport of the particles is involved. These artefacts, which so far have escaped the attention of investigators, can develop whenever geometric detection efficiency is less than 100%. As such peaks may be misinterpreted as new physics, their generation is investigated, both analytically and experimentally, for various detector configurations, including those used in searches for the spontaneous decay of the vacuum in heavy-ion collisions.
Gesehen am 28.04.2020